2000
DOI: 10.1080/13546800050199720
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect semantic priming with neutral and emotional words in schizophrenia: Relationship to delusions

Abstract: Introduction. Evidence is accumulating that suggests that semantic networks are abnormal in schizophrenia. Methods. To investigate this further, we examined priming in 42 schizophrenics and 28 normal controls on a lexical decision task involving three different prime-target conditions all at 700 ms stimulus onset asynchrony (SOA): directly semantically related, indirectly semantically related, and unrelated; and three types of emotional pairings: positive, negative, and neutral. Two schizophrenic groups were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 48 publications
3
36
0
Order By: Relevance
“…However, the requirement to manipulate trial valence (prime word valence) while holding associative strength between primes and targets constant was not met by many studies that implemented both semantic and evaluative priming (De Houwer, Hermans, Rothermund, & Wentura, 2002;Matthews, Pitcaithly, & Mann, 1995;Matthews & Southall, 1991;Rossell, Shapleske, & David, 2000;Spruyt, Hermans, De Houwer, & Eelen, 2004).^ Research by Rossell and Nobre (2004) is a good example to illustrate this issue. They used word pairs from different affect categories (neutral, happy, fearful, and sad) as primes and targets in a lexical decision task (e.g., prime MERRY, target HAPPY) and found priming for neutral and happy prime-targets pairs but not for fearful words (Rossell & Nobre, 2004).…”
Section: Previous Studies On the Interplay Between Semantic And Evalumentioning
confidence: 97%
“…However, the requirement to manipulate trial valence (prime word valence) while holding associative strength between primes and targets constant was not met by many studies that implemented both semantic and evaluative priming (De Houwer, Hermans, Rothermund, & Wentura, 2002;Matthews, Pitcaithly, & Mann, 1995;Matthews & Southall, 1991;Rossell, Shapleske, & David, 2000;Spruyt, Hermans, De Houwer, & Eelen, 2004).^ Research by Rossell and Nobre (2004) is a good example to illustrate this issue. They used word pairs from different affect categories (neutral, happy, fearful, and sad) as primes and targets in a lexical decision task (e.g., prime MERRY, target HAPPY) and found priming for neutral and happy prime-targets pairs but not for fearful words (Rossell & Nobre, 2004).…”
Section: Previous Studies On the Interplay Between Semantic And Evalumentioning
confidence: 97%
“…This is speculated to be due to schizophrenia patients producing fewer meaning based associations between words, and making more indirect associations than do controls (Moritz et al, 2001;Spitzer, 1997). Such findings make sense when the symptomatology of schizophrenia is considered; thinking in schizophrenia is often described as being disorganized, loose and mediated by indirect associations (Rossell et al, 2000). This may be due to the illogical storage of semantic information, in that, the nodes in the semantic network are aberrantly linked and indirectly associated words are stored within close proximity to each other (Rossell and David, 2006).…”
mentioning
confidence: 89%
“…The literature regarding semantic priming in schizophrenia is inconsistent (Rossell et al, 2000); some authors report increased priming (Moritz et al, 2001), whereas others report decreased priming (Condray et al, 1999;Rossell et al, 2000) and last, some authors suggest that patients diagnosed with schizophrenia exhibit no differences in priming when compared with healthy individuals (Henik et al, 1992). These inconsistencies have been attributed to a number of confounding factors that limit research with symptomatic clinical patients, including illness duration and medication usage (Moritz et al, 2001).…”
mentioning
confidence: 98%
“…Thereby, it was proposed that the influence of emotional nodes is restricted to the retrieval of episodic memory events [Macleod, 1987]. Nevertheless, other studies revealed that there were facilitative effects of mood induction on lexical decisions [Haenze and Hesse, 1993;Hesse and Spies, 1996], weaker or no effects of affective information in comparison to semantic informatzion [Kemp-Wheeler and Hill, 1992;Matthews and Southall, 1991;Siegle et al, 2002], greater priming effects for negative emotional information [Matthews et al, 1995;Windmann et al, 2002], or greater effect for positive emotional information [Rossell et al, 2000]. To conclude, the existing behavioral studies revealed heterogeneous results but they also showed that emotional valence does have a specific influence on semantic processing.…”
Section: Introductionmentioning
confidence: 97%